A bibliometric analysis of chlorpyrifos adsorption research: global trends, knowledge gaps, and future perspectives - Soujanya Shetty; Thivaharan Varadavenkatesan; Raja Selvaraj; Ramesh Vinayagam (Discover Applied Sciences)
Abstract Chlorpyrifos, a widely used agricultural insecticide, increases crop yield but significantly contributes to water pollution. Adsorption has emerged as an effective method for removing chlorpyrifos residues from water, offering a sustainable solution to this environmental challenge. This bibliometric review analyzes 73 publications extracted from the Web of Science Core Collection, focusing on chlorpyrifos removal via adsorption. Using tools like VOSViewer and Bibliometrix, we mapped the scientific landscape, identifying trends and research gaps. The analysis highlights that India and Egypt are the primary contributors, with the Journal of Environmental Chemical Engineering and Chemosphere being the leading journals in the field. Biochar, activated carbon, and nanoparticles are the most studied adsorbents for chlorpyrifos removal. The study also identifies influential authors, organizations, and funding sources, and provides insights into future directions for research in chlorpyrifos remediation.